Dynamic manufacturing : - Hayes, Robert H. (Free Press ;,Collier Macmillan, 1988)
Dynamic Manufacturing explores in depth such key infrastructure issues as capital budgeting, performance measurement, organizational structure, and human resource management, demonstrating how they interact to foster productivity growth, new product development, and competitive advantage. The book shows today's managers how to implement the changes that must be made if they want to create a truly superior manufacturing company. Taking concerned, committed managers step-by-step on the path toward better products, lower costs, and increased profits, this seminal work provides a road map for manufacturing firms seeking to build a competitive advantage through manufacturing excellence.